Chilli Thrips (castor thrips, Assam thrips, yellow tea thrips, strawberry thrips), Scirtothrips dorsalis Hood, Provisional Management Guidelines - Dakshina R. Seal; Waldemar Klassen (EDIS)
Adult thrips are small about 0.5 – 1.2 mm long. It is difficult to recognize this thrips with the naked eye, and definitive identification is best accomplished at approximately 40 to 80 x magnification. Eggs are about 0.075 mm long and 0.070 mm wide, and are inserted inside plant tissue. The egg stage lasts for 6-8 days, which is followed by two larval stages (1st and 2nd instars) that last for 6-7 days. The prepupal period is short (~ 24 h) and the pupal period lasts 2-3 days. The larvae are off-white. Also the adults are pale yellow to grayish-white in color with incomplete dark stripes on the dorsal surface where adjacent abdominal segments meet. The life cycle is completed in 14-20 days. The chilli thrips female oviposits 60 to 200 eggs in her life time at the rate of 2-4 eggs per day. This document is ENY-725 (IN638), one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: November 2005.